Elongated uvula and diagnostic utility of spirometry in upper airway obstruction - Paliwal Rajiv; Patel Satish; Patel Purvesh; Soni Hiren (Lung India, 2010)
Elongated uvula is relatively an uncommon condition. Upper airway obstruction is often a missed complication of such a rare condition. Clinical presentations of upper airway obstruction often mimic asthma. Hence it is very easily mis-diagnosed as asthma. Spirometry offers a very simple test to diagnose upper airway obstruction very early and easily. Once diagnosed, the management of elongated uvula, almost exclusively, is surgical excision leading to total cure. Here is a case report of such a rare condition.